미세플라스틱 필름의 프로시미돈과 3,5-다이클로로아닐린 흡착 특성 - 양지원; Ji Won Yang; 이연준; Youn-jun Lee; 조은혜; Eun Hea Jho (Hanguk hwangyeong nonghak hoeji, 2023)
Microplastics are generated by the breakdown of plastic wastes in agricultural soil and residual pesticides in agricultural soil can adsorb on microplastics. In this study, the sorption characteristics of procymidone (PCM) and one of its metabolites, 3,5-dichloroaniline (DCA), on low-density polyethylene (LDPE) and polyvinyl chloride (PVC) microplastics were investigated. The sorption and desorption tests were carried out for 72 h using LDPE or PVC microplastic films to study the sorption isotherms of PCM and DCA and kinetics for sorption and desorption of PCM. The results show that the sorption data of PCM and DCA were better described by the Freundlich isotherm model (R 2 =0.7568-0.9915) than the Langmuir isotherm model (R 2 =0.0545-0.5889). The sorption potential of PVC for both PCM and DCA was greater than that of LDPE. The sorption data of PCM on PVC and LDPE were fitted better to the pseudo-second- order kinetic model than the pseudo-first-order kinetic model. The PCM sorption on LDPE was about three times faster than that on PVC. Both microplastic films released the sorbed PCM back to water, and more PCM was released from PVC than LDPE, but the desorption rate was faster with LDPE than PVC. Overall, the results show that different microplastics have different sorption characteristics for different chemicals. Also, the sorbed chemicals can be released back to environment suggesting the potential of contaminant spread by microplastics. Thus, the management practices of microplastics in agricultural soil need to consider their interaction with the chemical contaminants in soil.